DAMPAK PANDEMI COVID-19 TERHADAP KEUNTUNGAN USAHATANI SAYURAN ORGANIK BERDAUN - Wula, Maria Goreti; Nurwiana, Ida; Un, Paulus (Buletin Ilmiah Impas, 2024)
The Covid-19 pandemic began in March 2020, this outbreak has shocked the whole world and entered Indonesia for the first time. The impact of the Covid-19 pandemic is being felt in all sectors, including the agricultural sector, including organic vegetables farmering businesses. This research aims to: 1) Knowing the benefits of farming organic leafy vegetables (kaylan, pakcoy, red spinach) before the pandemic and during the Covid-19 pandemic; 2). Knowing the feasibility of farming organic leafy vegetables (kaylan, pakcoy, red spinach) before the pandemic and during the Covid-19 pandemic and 3). Knowing the production trends of organic leafy vegetables farming businesses. The research method uses the survey method. CV GS Organic was chosen as the research location, determined deliberately (purposive sampling) with the consideration that is it a fairly large producer of organic vegetables.. The research results show that the profit from organic leafy vegetables before the covid-19 pandemic, kaylan vegetables, was Rp.41.221.989,-/Ha/year, pakcoy amounting to Rp. 12.730.322,-/Ha/year and red spinach amounting to Rp.9.617.822,-/Ha/year. During the Covid-19 pandemic, profits from kaylan vegetables increased to Rp.47.166.433,-/Ha/year, pakcoy amounting to Rp. 14.808.100,-/Ha/year and red spinach amounting to Rp.11.406.046,-/Ha/year. Value R/C ratio before the Covid-19 pandemic for farming kaylan vegetables was 2,60, pakcoy 1,55 and red spinach 1,47, meaning that the organic vegetables business kaylan, pakcoy, red spinach is financially feasible to cultivate. The trend in organic leafy vegetable production during the Covid-19 pandemic has a positive trend.